From Campaign to Habit: The Impact of Library Promotion on Students' Reading Interest at SD Negeri Mulo II Wonosari - Supiyatmi, Supiyatmi (Journal of Digital Scholarship in Archives and Information, 2025)
Background: The library plays an important role in supporting the teaching and learning process at SD Negeri Mulo II Wonosari, which has a large number of students and requires guidance to improve reading interest.Aims: To determine the extent of the library’s role in increasing students’ reading interest at SD Negeri Mulo II Wonosari.Methods: This study uses a qualitative descriptive approach with data collected through observation, interviews, and documentation.Results: The findings show that the library employs several promotional strategies, including book exhibitions, read-aloud sessions, reading corners, mandatory 15-minute reading activities, group discussions, and participation in the School Literacy Movement (SLM). These initiatives have successfully encouraged students to visit the library more frequently, borrow books, and participate in literacy programs. Read-aloud sessions and reading corners were found to be the most effective approaches. However, challenges such as limited collections, inadequate facilities, low teacher involvement, and restricted library hours reduce the optimal impact of these programs.Conclusion: Library promotion strategies have a significant positive influence on students’ reading interest and early reading habits. Enhancing collaboration among librarians, teachers, and school administrators, improving facilities, and expanding book collections are essential for sustaining literacy development. Future research could employ mixed methods to explore long-term literacy outcomes and behavioral changes in students' reading practices.